Systematization of Nursing Care - potentialities recognized by nurses of a public hospital - Ivete Maroso Krauzer; Francine Lima Gelbcke (Universidade Federal de Santa Maria, 2011)
This study aimed at identifying the profile of nurses from a public hospital of Santa Catarina, the contents which they received about the Systematization of Nursing Care (SNC) during their graduate course and the enabling aspects from SNC. It is about a qualitative, exploratory and descriptive research, carried out through 24 interviews, using a semi-structured questionnaire. The data was discussed by content analysis. The results pointed out that most interviewees were young nurses, specialists, recently graduated, working at the hospital institution from 04 months to 15 years, coming from Brazilian southern universities. They theoretically knew the SNC; experimented with the steps of the scientific method during their graduate course and recognized some nursing theorists. The SNC potentialities were the appreciation and the recognition of nursing as a profession and the promotion in the improvement of the assistance quality which contributes to nursing learning. The knowledge is compatible to the current national curricular guidelines for nursing teaching